'Half Tiger': An interrogation of digital and mobile street culture and aesthetic practice in Johannesburg and Nairobi. Issue 3 (1st December 2013) - Bristow, Tegan
In South African slang 'Half-Tiger' refers to five rand, half of a 'Tiger' (ten rand) and amounts to approximately 60 US cents. It is at the 'Half-Tiger' level of commerce where contemporary and deeply afro-urban digital cultural practice is found. A mass street level culture that in East Africa is driven by the mobile phone as socio-political development tool. And in South Africa by a booming media industry that has been hacked and gone viral. These cultures augment music, fashion, politics and social shifts with a digital aesthetic unique to each city. The article addresses mobile and digital culture in the two cities and compares the effect of mobile technology and its residue in the cultural practices of these very diverse urban environments. I will be addressing the work of key artists and musicians, looking closely at how they respond aesthetically and in a uniquely afro-urban way to a shifting engagement with digital mobile media and networked social practices.